2012
DOI: 10.1111/j.1468-1331.2012.03850.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset myasthenia not on the increase: a nationwide register study in Denmark, 1996–2009

Abstract: Late-onset MG comprised a large proportion of all incident cases in Denmark, was more common in men than women, and occurred with a stable incidence in the 14-year study period. Therefore, we speculate whether previous reports of a rise in late-onset MG reflect a non-biological phenomenon, that is, a gradual improvement in the diagnosis of MG in this age group in previous years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
31
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 17 publications
9
31
1
3
Order By: Relevance
“…In the Dutch MG population, we confirmed a rise in occurrence in the elderly in the Netherlands compared to a study from the same area 10 years ago [5] . Two repetitive populationbased studies are inconclusive regarding whether the late-onset subgroup really is rising [10,31,32] and claim that it most certainly is due to an increased awareness of MG in the elderly and better diagnostics and casefinding methods. We have controlled the typical methodological bias in our study and found more LOMG in the Netherlands than in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…In the Dutch MG population, we confirmed a rise in occurrence in the elderly in the Netherlands compared to a study from the same area 10 years ago [5] . Two repetitive populationbased studies are inconclusive regarding whether the late-onset subgroup really is rising [10,31,32] and claim that it most certainly is due to an increased awareness of MG in the elderly and better diagnostics and casefinding methods. We have controlled the typical methodological bias in our study and found more LOMG in the Netherlands than in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide Danish registries offer unique opportunities to identify myasthenia patients [11,12], track their use of drugs over long periods and ascertain myasthenia patients who develop cancer including NMSC. These unique data sources were used to examine the association between azathioprine use in myasthenia patients and risk of NMSC in a nationwide case-control study.…”
Section: Settingmentioning
confidence: 99%
“…Data from the above registries were retrieved and our validated method was used [11,12] to classify subjects as myasthenia patients from the date they fulfilled at least two of the following three criteria: (i) a primary diagnosis code of myasthenia in the Patient Registry, (ii) at least two pyridostigmine prescriptions in the Prescription Registry and (iii) a positive AChR-ab test.…”
Section: Identification Of Myasthenia Patientsmentioning
confidence: 99%
“…Over the past 2 decades, there has been increasing recognition of MG manifesting in individuals >50 years of age. Data from Denmark, Norway, and the UK suggest this was previously underappreciated . However, the finding of a very sharp peak in incidence rates (IRs) in those aged 75–79 years living in the UK has raised the possibility of a “cohort effect” and that an environmental exposure may increase the risk for developing seropositive MG .…”
mentioning
confidence: 99%